2021
DOI: 10.1098/rsob.210002
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial intermembrane space: the most constricted mitochondrial sub-compartment with the largest variety of protein import pathways

Abstract: The mitochondrial intermembrane space (IMS) is the most constricted sub-mitochondrial compartment, housing only about 5% of the mitochondrial proteome, and yet is endowed with the largest variability of protein import mechanisms. In this review, we summarize our current knowledge of the major IMS import pathway based on the oxidative protein folding pathway and discuss the stunning variability of other IMS protein import pathways. As IMS-localized proteins only have to cross the outer mitochondrial membrane, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 145 publications
(220 reference statements)
0
20
0
1
Order By: Relevance
“…There are parallel studies from plants [16] and most recent advances are made from other eukaryotic supergroups including excavatae that includes many pathogenic protists [17][18][19][20]. Previous studies from fungi, mammals, and plants revealed that at least eight protein complexes are required to traffic proteins to different locations in mitochondria (Figure 1); (1) TOM complex imports most of the mitochondrial proteins [21], (2) the sorting and assembly (SAM) complex in the MOM imports and assembles MOM β-barrel proteins [22], (3) MOM protein import (MIM) complex imports other MOM proteins with α-helical TMDs [23], (4) mitochondrial IMS assembly (MIA) complex is required for import and folding of several IMS-proteins [12], (5) TIM23 and (6) TIM22 are two major translocases of the MIM that imports proteins to the matrix, MIM and IMS [24,25], (7) presequence translocase associated motor (PAM) complex mediates translocation of preproteins to the matrix at expense of ATP hydrolysis [26], and (8) cytochrome oxidase assembly (OXA) complex inserts/imports some MIM proteins [27] (Table 1). Most of these translocases are multi-protein complexes (Table 1).…”
Section: Mitochondrial Protein Translocasesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are parallel studies from plants [16] and most recent advances are made from other eukaryotic supergroups including excavatae that includes many pathogenic protists [17][18][19][20]. Previous studies from fungi, mammals, and plants revealed that at least eight protein complexes are required to traffic proteins to different locations in mitochondria (Figure 1); (1) TOM complex imports most of the mitochondrial proteins [21], (2) the sorting and assembly (SAM) complex in the MOM imports and assembles MOM β-barrel proteins [22], (3) MOM protein import (MIM) complex imports other MOM proteins with α-helical TMDs [23], (4) mitochondrial IMS assembly (MIA) complex is required for import and folding of several IMS-proteins [12], (5) TIM23 and (6) TIM22 are two major translocases of the MIM that imports proteins to the matrix, MIM and IMS [24,25], (7) presequence translocase associated motor (PAM) complex mediates translocation of preproteins to the matrix at expense of ATP hydrolysis [26], and (8) cytochrome oxidase assembly (OXA) complex inserts/imports some MIM proteins [27] (Table 1). Most of these translocases are multi-protein complexes (Table 1).…”
Section: Mitochondrial Protein Translocasesmentioning
confidence: 99%
“…Most of the mitochondrial proteins are in the MIM and the matrix thus require crossing both membranes [8]. The MOM and IMS also possess several important proteins [11,12]. Proteins are translocated through TOM and TIMs either as fully or partially unfolded conditions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins destined for the IMS take the route of the MIA pathway ( Figure 1 and Table 1 ), which has been reviewed in great detail previously [ 54 ]. This class of proteins lack an MTS, are generally small, and share a conserved coiled coil-helix1-coiled coil-helix 2 domain (CHCHD).…”
Section: Protein Translocationmentioning
confidence: 99%
“…This class of proteins lack an MTS, are generally small, and share a conserved coiled coil-helix1-coiled coil-helix 2 domain (CHCHD). These cysteine-rich proteins contain two pairs of cysteines separated by three or nine amino acid residues (Cx 3 C or Cx 9 C) in the helices [ 54 ]. The small TIM chaperones of the IMS, important for translocase of the inner mitochondrial membrane 22 (TIM22)-dependent translocation described below, and assembly factors of IMM proteins, such as the respiratory complexes (see below and Table S1 ), are some examples of MIA substrates.…”
Section: Protein Translocationmentioning
confidence: 99%
“…Distinct conformations of the TIM23 complex have been identified that aid either the translocation of large hydrophilic domains across the inner membrane to the matrix, or the lateral diffusion of transmembrane α-helices into the lipid bilayer (Schendzielorz et al, 2018;Edwards et al, 2021). Key to these differing conformations are the TIM23 accessory proteins Pam18 and Mgr2.…”
Section: Protein Assembly By the Translocon Of The Inner Membranementioning
confidence: 99%